La ciudad como refugio y motor de la biodiversidad. - Salvo-Tierra, Ángel Enrique (My University, 2025)
It is more than evident that we are at the beginning of a change of era. A change very similar to the transition from the Gothic to the Renaissance. Then it was brought about by the printing press, naval advances and the connection with other continents, and today it is brought about by Artificial Intelligence, aeronautics and the race towards the outside world. Its consequences are to be expected, as then, to be a rebirth, a profound transformation in the way human beings conceive the world, knowledge, art and life in general. The turning point towards this era of change was anticipated by Crutzen and Stoermer (2000) as the Anthropocene, defined by technological progress, the multiplication of production and consumption, and explosive population growth thanks to improvements in food and health. For some authors, this global population growth acquires, in a misanthropic but realistic vision, a behaviour similar to that of a ‘plague’ (Rodriguez Anido et al. 2024). James Lovelock (2021) in his latest major essay, Novacene: The Coming Age of Hyperintelligence, goes even further, and as he already advanced in Gaia (1985), he draws a conceptually different world, which we are approaching at breakneck speed. According to his analysis, the new era that is now beginning will no longer have only life forms based on RNA and DNA codes, but on other codes based on digital electronics, what he calls cyborgs (free thinkers without the encumbrance of human rules), which will cause us to lose our status as the most intelligent and dominant creatures on Earth, and the only ones in the Universe. In both the Anthropocene and the Novacene, the question centres some of its extremes on the fact that, while the demographic growth of our species is unconscionable, at the same time the concentration of individuals in collective habitats is unique, in an evolution similar to that of other eusocial species (Harrison et al. 2018).
Conferencia inaugural en el 51º CONGRESO NACIONAL DE LA ASOCIACIÓN DE PARQUES Y JARDINES
Keywords: Bioclimatología; Flora urbana; Biodiversidad; Ecología urbana; Zonas verdes; Urban ecology; Isla de Calor; Infraestructura verde urbana; Diversidad ecológica